2012
DOI: 10.1111/j.1365-2435.2012.01995.x
|View full text |Cite
|
Sign up to set email alerts
|

Stability of tallgrass prairie during a 19‐year increase in growing season precipitation

Abstract: Summary1. Precipitation is considered to be a key driver of ecosystem processes in mesic grasslands, and climate models predict changes in the amount and intensity of precipitation under future global change scenarios. Although most experimental rainfall studies decrease precipitation, seasonal rainfall is predicted to increase in the northern Great Plains under climate change. 2. We analysed changes in community composition and structure of upland and lowland native tallgrass prairie in central Kansas, USA, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
115
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(124 citation statements)
references
References 87 publications
(180 reference statements)
6
115
3
Order By: Relevance
“…Whereas several previous studies have reported relatively high resistance to climatic changes in unproductive ecosystems (13,14,30,47,48), ours is among the first to identify resource colimitation as the mechanism responsible for this resistance.…”
Section: Discussionmentioning
confidence: 58%
“…Whereas several previous studies have reported relatively high resistance to climatic changes in unproductive ecosystems (13,14,30,47,48), ours is among the first to identify resource colimitation as the mechanism responsible for this resistance.…”
Section: Discussionmentioning
confidence: 58%
“…Research from Mediterranean systems (Zavaleta et al 2003a, c) and tall-grass prairie (Collins et al 2012) found that increased precipitation had a small positive or negligible effect, respectively, on species richness. Similar findings have been reported in China (Yang et al 2011a, b).…”
Section: Bioclimatic Conditionsmentioning
confidence: 99%
“…This is a novel finding because other studies in grasslands (Hsu et al, 2012) have shown that grasses alone have a negative response to increasing interannual rainfall variability in wet environments. Grasses typically have a high growth rate especially in wet environments (Teuling et al, 2010;Collins et al, 2012;Xu et al, 2015), consistent with the concept of the world-wide 'fast -slow' plant economics spectrum (Reich, 2014); thus, grasses could quickly take advantage of the window of opportunity existing in years with above average precipitation. The high growth rate in grasses increases fire frequency and fire-induced tree mortality (Bond et al, 2008;Ratajczak et al, 2014), thereby leading to a reduction in tree competition with grasses for soil water, which further favors grass biomass.…”
Section: The Effects Of Interannual Rainfall Variability On Tree-grasmentioning
confidence: 88%
“…Fluctuations in resource/rainfall availability could provide windows of opportunity in resource enrichment and thus species (i.e., grasses) with a high growth rate may quickly take up resources, change the disturbance regime (i.e., fires), and then invade or dominate the landscape (e.g., Davis et al, Davis and Melissa, 2001;Corbin and D'Antonio, 2004). However, opposite interactions may occur in arid environments where grasses exhibit slow growth rates (e.g., Teuling et al, 2010;Collins et al, 2012). Indeed, recent field studies at the Jornada Basin (New Mexico) show that increasing interannual rainfall fluctuations could favor shrubs over grasses (e.g., Gherardi and Sala, 2015 a b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation